Stock and Sovereign Returns Linkages: Time-Varying Causality and Extreme-Quantile Determinants - António Afonso; José Alves; Wojciech Grabowski; Sofia Monteiro (CESifo GmbH, 2025)
We employ a cross-quantilogram approach to assess relationships between quantiles of stock returns and sovereign yields, in the U.S. and Germany, in the period 1990-2024. Specifically, we focus on the lowest 5% quantile of stock returns and the highest 5% quantile of bond returns, providing insights into tail dependencies, crucial during market downturns and periods of heightened volatility. We also measure causality in volatilities extending well-known approaches analyzing volatility transmission. We find significant cross-market relationships between U.S. and German stock and bond markets, influenced by economic crises, macroeconomic dynamics, and monetary policy interventions, and financial stress play a crucial role.
Keywords: C32; F21; F37; F42; 330; stock returns; sovereign bond returns; stock-bond relationship; cross-quantilogram; volatility transmission; US; Germany; monetary policy shocks; fiscal stance